Heterogeneity in the Cost Structure of Water and Sanitation Services : A Cross-Country Comparison of Conditions for Scale Economies - Nauges, Celine; van den Berg, Caroline (2012)
The main purpose of this article is to compare the cost structure of water utilities across a set of 14 countries with different levels of economic development. As far as is known, the cross-country perspective is novel in this literature. This article first provides new measures of returns to scale in the water and sanitation sector for a set of countries, most of them from the developing world. It is then shown that the probability of a utility operating under decreasing, constant, or increasing returns to scale depends not only on its characteristics (the volume of water produced in particular), but also on the country's level of economic development (gross national income) and business environment as measured by investor protection, the cost of enforcing contracts and perceptions of corruption.